Bimbingan Teknis Penggunaan Teknologi Berbasis IoT dalam Upaya Perawatan Kawasan Wisata Setu Babakan - Prasetya, Yuli; Angellia, Filda; Cahya, Waskita; Silvanie, Astried; Permana, Dwi Sidik; Kurniawan, Ari; Ladjamuddin, Siti Madinah; Hasibuan, Moh. Sanjiva Refi (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2025)
This Abdimas activity aims to introduce Internet of Things (IoT)-based technology in the management of the Setu Babakan cultural tourism area, with a focus on creating an automatic plant watering device. The program involves area managers and local communities who are provided with training on the basics of IoT and the application of this technology in assembling a watering device that functions automatically based on soil moisture. The methods used include theoretical training, hands-on assembly practice, and field testing. The results of the activity show that the automatic watering device can improve the efficiency of plant management, reduce manual labor, and support environmental sustainability through more efficient water usage. Despite facing some technical challenges, participants were able to overcome them and gained a deeper understanding of the application of technology in tourism area management. This program also opens up opportunities for further development in the field of environmentally friendly technology that can be applied to other tourism areas. In conclusion, this community service provides a positive contribution to the management of Setu Babakan and can be further developed for broader application.